Tsenguluso ya maipfi ane a khou ngalangala kha Tsivenda - Mudau, Mmbulaheni Lawrence (My University, 2012)
The title of the research topic is Tsenguluso ya maipfi ane a khou ngalangala kha Tshivenḓa. A multilingual society as South Africa compels a variety of communities to interact with one another. This impacts on languages as well. Tshivenḓa has not escaped this phenomenon as it constantly adopts many words from its sister languages and English in order to cope with the demands of modernity. The study would like to examine this phenomenon as a way of trying to establish the advantages and disadvantages of phasing out what might be termed archaic words and adopting new terms
Thesis (M.A. (African Languages)) -- University of Limpopo, 2012
Keywords: Archaisms (Linguistics); Venda language -- Archaisms; Venda language -- Obsolete words